Study on Rural Breast Cases in Sarawak : Patient Case Record Review Approach - Ho, Pei Sze; Haslan, Ottot; Ahmad Tirmizi, Jobli; Dayang Affizah, Awang Merikan (2023)
Breast cancer as a non-communicable disease, amplified disease burden among rural populations with limited access to healthcare resources. This research study focuses on investigating the disparities in treatment costs for breast cancer patients residing in rural areas of Sarawak, Malaysia, employing a comprehensive analysis of patient case notes. Additionally, the study evaluates the disability-adjusted life years (DALYs) associated with treatment costs, offering valuable insights into the overall disease burden and cost-effectiveness of interventions. Data is gathered from a representative sample of breast cancer patients' case notes in rural healthcare facilities across Sarawak. Stages of cancer, treatment type, duration, and medication and hospitalization expenses are analyzed to better understand the economic impact of breast cancer management in this underprivileged population. The research does adopt the DALYs framework to assess the disease burden linked to breast cancer treatment in rural Sarawak. By considering both mortality and morbidity aspects, DALYs provide a comprehensive metric to quantify the overall impact of the disease on patients and their communities. In this study, findings are expected to shed light on the financial challenges faced by rural breast cancer patients in accessing adequate treatment, as well as identify potential areas for cost-saving interventions and improved resource allocation.